Resenha: GUINZBURG, Jaime. Crítica em tempos de violência. São Paulo, Edusp, 2012. - Silva, Maurício (Revista Literatura em Debate, 2013)
Resenha: GUINZBURG, Jaime. Crítica em tempos de violência. São Paulo, Edusp, 2012.